2018
DOI: 10.1371/journal.pone.0192757
|View full text |Cite
|
Sign up to set email alerts
|

Effects of breast stimulation for spontaneous onset of labor on salivary oxytocin levels in low-risk pregnant women: A feasibility study

Abstract: ObjectivesThis preliminary study aimed to 1) determine changes in the salivary oxytocin (OT) level during breast stimulation for promoting the spontaneous onset of labor in low-risk term pregnancies, and 2) clarify the feasibility of the breast stimulation intervention protocol in terms of practicality and acceptability.MethodsWe used a single arm trial design. Sixteen low-risk pregnant women between 38 and 40 weeks of gestation with cephalic presentation participated. They performed breast stimulation for 3 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 32 publications
0
10
0
4
Order By: Relevance
“…Our previous feasibility study suggested the possible increase in salivary oxytocin level by breast stimulation on the third day of intervention [15]. Sixteen low-risk women in their late pregnancy participated in our previous study.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous feasibility study suggested the possible increase in salivary oxytocin level by breast stimulation on the third day of intervention [15]. Sixteen low-risk women in their late pregnancy participated in our previous study.…”
Section: Introductionmentioning
confidence: 99%
“…6.3% Kavanagh, Kelly e Thomas, 2005Singh et. al, 2014Demirel e Guler, 2015Takahata et. al, 2018 (2010), no estudo RTC de Singh et al, (2014) (Demirel & Guler, 2015;Kavanagh, Kelly &Thomas, 2005;Singh et al, 2014;Suja, 2015;Suresh e Soni, 2019;Takahata et al, 2018).…”
Section: Effects Of Breast Stimulation For Spontaneous Onset Of Labormentioning
confidence: 99%
“…al, 2014Takahata et. al, 2018Suja, 2015Suresh e Soni, 2019 deve existir pausa e descanso entre cada estimulação (Demirel & Guler, 2015;Kavanagh, Kelly & Thomas, 2005;Razgaitis & Lyvers, 2010;Singh et al, 2014;Suja, 2015;Suresh e Soni, 2019;Takahata et al, 2018). Para os ensaios analisados, identificamos e delineamos indicadores tradutores dos outcomes, eficácia e segurança, baseados nas diretrizes internacionais (ACOG, 2019;NICE, 2019, OMS, 2018.…”
Section: Effects Of Breast Stimulation For Spontaneous Onset Of Laborunclassified
See 1 more Smart Citation
“…Mengacu pada penelitian terdahulu yang dilakukan oleh Takahata (2018) di Jepang dan Abedi (2016) menyatakan bahwa sekitar 50% wanita hamil yang melakukan olahraga stimulasi payudara dapat membantu menginduksi persalinan spontan sehingga tidak mengeluarkan biaya yang mahal dan Oksitosin serta prostaglandin merupakan hormon yang bertanggung jawab penuh atas kontraksi uterus selama tahap ketiga persalinan. Assad (2016) di India menyampaikan bahwa Oksitosin yang dihasilkan akibat adanya rangsangan akan menghasilkan spektrum yang fungsinya dapat memfasilitasi kelahiran di inersia uterus, mencegah perdarahan setelah kelahiran.…”
Section: Analisis Bivariatunclassified